Time lapse imaging: is it time to incorporate this technology into routine clinical practice?. (3rd April 2017) - Bhide, Priya; Maheshwari, Abha; Cutting, Rachel; Seenan, Susan; Patel, Anita; Khan, Khalid; Homburg, Roy
Abstract: Time-lapse imaging (TLI) systems for embryo incubation, assessment and selection are a novel technology available to in vitro fertilization (IVF) clinics. However, there is uncertainty about their clinical and cost-effectiveness and insufficient good quality evidence to warrant their routine use. Despite this, enthusiastic commercial marketing and slipping clinical equipoise have led to the widespread hasty introduction of this technology into practice, often at a considerable expense to the patient. We have reviewed the published literature and aim to summarize the strengths, weaknesses, opportunities and threats of these systems. These specialized incubators provide undisturbed embryo culture conditions and, by almost continuous monitoring of embryo development, generate morphokinetic parameters to aid embryo selection. They are thus hypothesized to improve outcomes following IVF. Although literature reports improved reproductive outcomes, these outcomes are largely surrogate and there is a paucity of studies reporting live births. The use of time lapse systems may reduce early pregnancy loss, increase elective single embryo transfers and limit multiple pregnancies through better embryo selection. However, the quality of the studies and hence the evidence so far, is low to moderate quality. We recommend further research producing robust high-quality evidence for and against the use of these systems.